Thematic analysis of sexuality in the school context with teachers of basic education - Laine Gomes Chaveiro; Laurena Moreira Pires; Marcos André Matos; Sheila Araújo Teles; Sandra Maria Brunini Souza; Márcia Maria Souza (Universidade Federal do Ceará, 2015)
Objective: to identify content related to the sexuality theme at schools from municipal and state networks; and to identifythe difficulties and needs of teachers in the approach to this theme. Methods: cross-sectional study with 79 teachersof educational institutions using self-administered questionnaire. For analysis one used as an endpoint to belong to themunicipal or state school networks. Result: most teachers work in the state school network. The theme sexuality is not dealtwith as recommended by the National Curriculum Parameters. Teachers from the municipal network deal more with thepregnancy issue (p=0.04), and it was more mentioned by the state system teachers for training (p=0.03). Most do not haveexperience and training in the subject (p=0.04). Conclusion: partnerships with the health area are necessary for teachers'training. It is also important to recognize the work of nurses in the work of sex education as an essential component in thecomprehensiveness of care in order to strengthen the area of school health.